Ethanol-induced increase in drug acetylation in man and isolated rat liver cells. - Olsen, H (1978)
Sixteen healthy volunteers took part in a cross-over study examining the effect of ethanol on the rate of sulphadimidine acetylation (blood ethanol concentration about 1 g/1). In both rapid and slow acetylators the apparent half life of the drug decreased by about 20% after ethanol (mean reduction 39 +/- SE 8 min) and the amount of drug acetylated, measured in blood and urine, increased. In three slow acetylators the rate of acetylation in blood increased so noticeably after ethanol that they would otherwise have been classified as rapid acetylators. Suspensions of isolated rat liver cells showed an increase of about 30% in the rate of sulphadimidine acetylation after the addition of ethanol (2 g/1). Patients' usual alcohol consumption should be taken into account in determining their acetylator status.